(untitled) (Journal of Human Sciences, 2021)
This This study has revealed the aspirations of some of the colonizing countries like Britain and France, and their attempts to control the middle of African continent, and making the state of western Tripoli as a spreading point towards the rest of the neighbouring areas being attributed to its political, and economical importance. As a consequence, Britain appointed Warrington as its consul in the state of western Tripoli who was careful and paid attention to the French activities in the Sahara. So he employed co-consuls on the trade roads in Mursik and Ghadamis. On the other hand, we found that France also worked to keep its influence in the country. It recruited Russo, as a consul in the state of western Tripoli who, since his arrival to the state, has worked to strength his influence to protect the status and presence of France in the state. This has led to a massive competition between the two consulates of France and Britain. The consuls’ influence strongly and noticeably increased in the state. Afterwards, when the Ottoman Empire uncovered the political conflict between the two mentioned countries, and the attempts of each of them to take a standing ground in the north of Africa, besides the disorder of the political, economical and social considerations in the country, this urged them to directly rule the country again in 1835, in fear of the country fall in colonization.